PENGARUH SIKAP KERJA, TEAM WORK DAN LOCUS OF CONTROL TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR CAMAT MUARA BANGKAHULU - Fauzan Fauzan (Creative Research Management Journal, 2018)
Research at the Muara Bangkahulu Sub-District Office with a sample of 25 employees, as the problem studied: how much influence work attitude, team work and locus of control have on employee work performance at the Muara Bangkahulu Sub-District Office. Work attitude is a behavior that distinguishes someone from others in carrying out work. Then the team work group of employees who work together to work together to complete the work that must be completed by an organization. Whereas Locus of control is an awareness of an employee is an employee's confidence that they are in control of the work they do. These three variables influence employee performance. Job performance itself is interpreted as the best work contributed by employees. Based on the results of the analysis obtained multiple correlation values ​​of 0.667 with termination of 0.464 indicates that the correlation of these variables is strong. The regression equation Y = 1.018 + 0.222 X1 +0, 391 X2 + 0.260 X3, this indicates that the influence of each independent variable on the large devendent variables. Partial test results (t test) and simultaneously (f test) indicate a significant influence on work attitude, team work and locus of control on employee performance.